2019
DOI: 10.1186/s12917-019-2169-1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intervention reduces left atrial enlargement in dogs with early preclinical myxomatous mitral valve disease: a blinded randomized controlled study in 36 dogs

Abstract: BackgroundMyxomatous mitral valve disease (MMVD), the most common naturally-occurring heart disease in dogs, is associated with alterations in energy metabolism, oxidative stress and inflammation. Energy deprivation plays a causal role in the development of heart failure. This study was designed to determine if a cardiac protection blend (CPB) of nutrients containing medium-chain triglycerides as an alternative energy source, fish oil to reduce inflammation, antioxidants, and other key nutrients important to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 54 publications
(59 reference statements)
1
22
2
Order By: Relevance
“…Many of the observed changes were likely due to the differences between diets which differed considerably in their FA compositions. However, clinical benefits from the intervention study suggested a potential association between these diet-induced molecular and metabolic changes and clinical outcomes [17]. PCA analysis showed a clear clustering between diet groups after 6 months while no clustering was observed at baseline.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Many of the observed changes were likely due to the differences between diets which differed considerably in their FA compositions. However, clinical benefits from the intervention study suggested a potential association between these diet-induced molecular and metabolic changes and clinical outcomes [17]. PCA analysis showed a clear clustering between diet groups after 6 months while no clustering was observed at baseline.…”
Section: Discussionmentioning
confidence: 92%
“…The study design of this blinded, randomized, placebo-controlled study, including detail on the diets, animals, husbandry and sampling protocols, was previously published [17]. The two study diets (control (CON) and CPB) were similar in protein, total fat, and carbohydrate contents: the MCTs and fish oil in the CPB diet were balanced with animal fats in the CON diet [17].…”
Section: Diets Animals and Study Designmentioning
confidence: 99%
See 3 more Smart Citations